O conceito de sociedade civil em Kant - Mesquita, Jéssica de Farias (2014)
This research aims to analyze the Kantian political philosophy from his writings about the law in the work Doctrine of Right. Thus, it begins by a thorough study about the state of nature, understood, in Kantian terms, as general law, to then introduce our attention on the concept of civil society. The development of the research revolves around property and contract, notions used to intermediate the relationship between natural law and positive law, the latter found only in public when governed by juridical laws. The concept of juridical ownership under the statute of law will also be examined, as this concept presents, in a more evident way, the juridical differences that permeate from the state of private nature of laws to the private political State formed by civil society. Kant identifies the man as a rational being capable of self-legislation and gifted with an innate freedom. However, despite all having freedom even in the private law, Kant draws attention to the need of this freedom to turn into an external freedom in the political sphere, in order to prevent the abuse of the freedom of one and another. The civil society not only has the law that interferes with the freedom of everyone in order to preserve the rules of law in Society, however, encompasses citizens that have to be conducted to a better collective organization.